2012
DOI: 10.1371/journal.pone.0034737
|View full text |Cite
|
Sign up to set email alerts
|

Ocean Acidification-Induced Food Quality Deterioration Constrains Trophic Transfer

Abstract: Our present understanding of ocean acidification (OA) impacts on marine organisms caused by rapidly rising atmospheric carbon dioxide (CO2) concentration is almost entirely limited to single species responses. OA consequences for food web interactions are, however, still unknown. Indirect OA effects can be expected for consumers by changing the nutritional quality of their prey. We used a laboratory experiment to test potential OA effects on algal fatty acid (FA) composition and resulting copepod growth. We sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
237
2
9

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 254 publications
(260 citation statements)
references
References 42 publications
12
237
2
9
Order By: Relevance
“…Therefore, all of the observed negative effects in the copepods here could be attributed to the direct changes in C content, rather than secondary biochemical changes in food quality. In contrast, the diatom Thalassiosira pseudonana contains less highly unsaturated fatty acids when grown under high pCO 2 conditions (Rossoll et al 2012). The authors also observed a decline in Fig.…”
Section: Discussionmentioning
confidence: 93%
“…Therefore, all of the observed negative effects in the copepods here could be attributed to the direct changes in C content, rather than secondary biochemical changes in food quality. In contrast, the diatom Thalassiosira pseudonana contains less highly unsaturated fatty acids when grown under high pCO 2 conditions (Rossoll et al 2012). The authors also observed a decline in Fig.…”
Section: Discussionmentioning
confidence: 93%
“…in food availability, phytoplankton community structure, size classes and stoichiometry (Suffrian et al, 2008;Feng et al, 2009;Rossoll et al, 2012). On the other hand MZP are known for a direct pH sensitivity (Hinga, 2002;, and a drop in seawater pH as a result of increasing pCO 2 could directly affect the physiology of both autotrophic and heterotrophic protists by changing, e.g.…”
Section: N Aberle Et Al: Tolerance Of Microzooplankton To Ocean Acimentioning
confidence: 99%
“…For instance, Teoh et al (2004) reported a significant decrease in polyunsaturated fatty acids (PUFA) at temperatures above 4 • C in an Antarctic strain of Navicula sp. In addition, cellular fatty acid (FA) composition and nutrient stoichiometry can be directly related to the food quality transferred to higher trophic levels and may be negatively affected by ocean acidification (Riebesell et al, 2000;Rossoll et al, 2012;Schoo et al, 2013). However little is known about the combined effects of ocean acidification and warming on microalgal lipid FA composition.…”
Section: Introductionmentioning
confidence: 99%